Juventude, música e regionalismo: ressignificações sobre o lugar nordeste - Falcao, Ana Paula Pereira (2010)
The present study has as object of analysis the young musical groups of the city of João Pessoa, that are fit into the musical gender MPB neo-regionalist, which articulate elements of the traditional musicality of the Northeast area with rhythms and languages of musical genres considered universal. The research had as objective to analyze the image of Northeast that is built over the musical production of those groups. That production is characterized by the hybridization of rhythms and timbers of the traditional musicality, with elements of a globalized culture, like, for instance, the use of electronic instruments and rhythms as jazz, rock, funk, reggae and ska. The theoretical-methodological way that was used was inspired by the Cultural Studies and by some elements of the Semiotics. The research demonstrated that those groups are building a new image of the Northeast area, that follows the contemporary articulations among the Northeast, Brazil and the New World Economical Order, likewise the intensified tourist flows. The contemporary musical scene of the city was characterized as well as the dialogues that the current groups establish with traditional icons of the regional music. also, The new forms of production and musical circulation of the city were emphasized in addition to the performance of the significant cultural agents, like the representatives of the State and SEBRAE. It was observed the consolidation of a neo-regional musical gender, that builds an image of the Northeast which comes out as a hybridized place, a mix of tradition and modernity, that is also a place of ambiguities involving poverty and violence living side by side with wealth, culture and exuberant nature.